2012
DOI: 10.1152/ajpgi.00406.2011
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin mediates endocytosis of progastrin and activates MAPKs: role of cell surface annexin A2

Abstract: Cell-surface-associated annexin A2 (CS-ANXA2) is a nonconventional "receptor" for progastrin; expression levels of both are elevated in colon cancers, and downregulation of either reduces tumorigenic potential of cells. We recently reported internalization of progastrin in target cells. Here, mechanisms mediating internalization of progastrin were examined. Initially, we confirmed that cell-surface ANXA2 mediates binding and internalization of progastrin in intestinal cells. Progastrin, covalently linked to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Interestingly, we found that CPZ, which has been reported to impair p38 MAPK activity (14), selectively decreases LPS-induced IL-6 production in cultured macrophages, and also inhibits LPS-induced Arid5a expression. It has been also reported that p38 is critical for IL-6 production in MEFs under IL-1β signaling (15).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, we found that CPZ, which has been reported to impair p38 MAPK activity (14), selectively decreases LPS-induced IL-6 production in cultured macrophages, and also inhibits LPS-induced Arid5a expression. It has been also reported that p38 is critical for IL-6 production in MEFs under IL-1β signaling (15).…”
Section: Discussionmentioning
confidence: 70%
“…S1C). Recently, CPZ has been reported to inhibit p38 signaling (14). Moreover, p38 signaling has been shown to be involved in IL-6 mRNA stability (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Indeed, the identity of a progastrin receptor remains an issue of intense investigation. Recent studies have suggested that Annexin A2, 32,33 ferric ions, 34 and charged glycosaminoglycans 17 are involved.…”
Section: Discussionmentioning
confidence: 99%
“…43 Cell-surface ANXA2 is required for the binding and internalization of progastrin in intestinal cells, potentially by clathrin-mediated endocytosis. 44 Intracellularly, ANXA2 is present on the plasma membrane and early endosome and interacts with actin to act as a regulator of membra-cytoskeleton dynamics. [45][46][47] It was reported that ANXA2 is involved in the phagocytosis of the shed photoreceptor outer segment by pigment epithelial cells in the retina.…”
Section: Discussionmentioning
confidence: 99%